Carotid Artery Cut-Down in Pediatric Cardiac Catheterization: When and How - Doyurgan, Onur; Akdeniz, Osman; Ozdemir, Fatih; Kilic, Yigit; Aldudak, Bedri (Tech Science Press, 2022)
Background: Vascular access used for pediatric cardiac catheterization is one of the most important factors that affects the success of the procedure. We aimed to compare the effect, success, and complications of cardiac catheterizations performed by carotid cut-down or femoral puncture in newborns or young infants. Methods: We included who underwent catheterization in our department between 28 January 2017 and 15 April 2021. These patients underwent balloon aortic valvuloplasty, balloon coarctation angioplasty, ductal stenting, diagnostic procedures for aortic arch pathologies, and modified Blalock-Taussig in-shunt intervention. Patients were divided into two groups: femoral puncture (group = 1) and carotid cut-down (CC, group = 2). Results: Seventy-two catheterization procedures were performed in 64 patients; 32 (44.4%) were performed via the femoral approach and 40 (55.6%) were performed via the carotid approach. Sixteen (22.2%) procedures were diagnostic and 56 (77.8%) procedures were interventional. CC was performed in 13 (32.5%) patients with failed femoral intervention. Patients in the CC group had shorter durations of procedure, vascular access, and anesthesia, compared with the femoral access group (80.9 and 116.2 min, p = 0.001; 12.9 and 22.5 min, p = 0.001; 140.9 and 166.6 min, p = 0.001, respectively). Patients who underwent CC had fewer complications than did patients in the femoral access group (2.5% and 21.8%, respectively; p = 0.01); larger sheats were used in CC patients (p = 0.028). Conclusion: The carotid artery can be successfully used as a primary catheterization route, particularly in patients with small body weight and patients who require rapid vascular access, or stenting of the vertical duct.
Keywords: Cardiac catheterization; carotid artery; cut-down; pediatric cardiology; surgery